Microfluidic deposition for resolving single-molecule protein architecture and heterogeneity - Francesco Simone Ruggeri (Nature Portfolio, 2018)
Manual sample deposition on a substrate can introduce artifacts in quantitative AFM measurements. Here the authors present a microfluidic spray device for reliable deposition of subpicoliter droplets which dry out in milliseconds after landing on the surface, thereby avoiding protein self-assembly.